Numerical study of wind-tunnel wall effects on lift and drag characteristics of NACA 0012 airfoil - Abobaker, Mostafa; M. Elfaghi, Abdulhafid; Addeep, Sogair (Akademia Baru Publishing, 2020)
Possible interference effects of the wind tunnel walls play an important role especially for measurements in closed-wall test sections. In this study, a numerical analysis of two-dimensional subsonic flow over a NACA 0012 airfoil at different computational domain heights, angles of attack from 0o to 10o , and operating Reynolds number of 6×106 is presented. The work highlights the role of computational fluid dynamics (CFD) in the investigation of wind tunnel wall effect on lift curve slope correction factor (Ka). The flow solution is obtained using Ansys Fluent software by solving the steady-state continuity and momentum governing equations combined with turbulence model k- shear stress transport (SST-Kω). The numerical results are validated by comparing with the available experimental measurements. Calculations show that the lift curve slope correction results are very close to the published data.